Individuation in decapitation with C7-T1 vertebral scanning - Etty Indriati, Etty Indriati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Mutilation to eliminate the identity of murder victim is often conducted in crimes, for instance by cutting the head from the body. In order to determine whether the head belongs to the same individual with the body, research on the vertebral anatomy of the seventh cervical and first thoracic vertebrae is very important to be conducted.Objective: to observe the morphological congruence between the seventh cervical vertebrae and the first thoracic vertebrae.Material and Method: Thirty skeletons housed at the Laboratory of Anatomy, Embryology and Anthropology Gadjah Mada University Faculty of Medicine, Yogyakarta. The methodology is by scanning the C7 and T1 with three-dimensional scanner Umax Astra 2000, which scanned the bones into two dimensional on scanning paper. The scanned C7 is superimposed to T1, in the same individual and also between individual. Result: High degree of congruence between C7-T1 occurred at lamina, the structure that connects the pedicle and spinous process. This congruence extends into the posterio-inferior lateral border at the interior articular facets. Superimposition of C7-T1 inter-individual showed no accordance on the spinous process, lamina, inter-vertebral foramen, transverse process, and corpus vertebrae. Thus there was no two individuals had the same size and contour of C7-T1.Conclusion: This research is important in determining individuation on decapitation homicide where the body is dispersed from the head. This study also shows the contribution of anatomy in forensic sciences.Key words: decapitation, individuation, congruence, vertebrae, scanning